JIZYA IN EASTERN TRANSCAUCASIA FROM THE 17TH TO THE FIRST HALF OF THE 19TH CENTURY - Kostikan, Kristine Petro; Stepanan, Gevorg Srapionovic; Tovmasan, Anait Araikovna (History, Archeology and Ethnography of the Caucasus, 2024)
This article aims to provide a comprehensive examination of jizya, the poll tax levied on non-Muslim populations in Eastern Transcaucasia from the 17th to the first half of the 19th century. This period encompasses the region’s governance under the Iranian Safavid and Nader Shah states, followed by local khanates before and after their incorporation into the Russian Empire. The methodological foundation of this study rests on an empirical analysis of primary sources, complemented by a review of relevant scholarly literature. The comparative-historical method is employed to analyze information from these sources. The article explores source data on jizya rates during the dominion of Safavid dynasty shahs and Nader Shah over Eastern Transcaucasia. Evidence regarding the poll tax imposed on non-Muslims in Muslim khanates, established in the region following Nader Shah’s fall, indicates that jizya collection persisted through the second half of the 18th century. In the Sheki Khanate, this practice continued even after its integration into the Russian Empire until the mid-19th century. The study reveals a significant increase in the poll tax rate in the Sheki Khanate during the latter half of the 18th century. In this khanate, jizya was renamed “abrishom-i din” (Persian – silk for faith) or “ipak dini” / “din ipaki” (Turkish – silk for faith). The increase in jizya rates in the Sheki Khanate reflected the religious intolerance of the local Hajji Chelebi Khan towards Christians, prompting many to convert to Islam. Based on the documents examined, the article argues that a burdensome tax policy was implemented against Armenians and Udins in the Sheki Khanate, persisting even after its incorporation into the Russian Empire until the mid-19th century.